ASSESSMENT STRATEGY BASED ON VALIDITY AND RELIABILITY IN DETERMINING THE MINIMUM COMPLETENESS CRITERIA FOR ISLAMIC RELIGIOUS EDUCATION - NurAzizi, M. Hafidz; Alfauzi, Akhmad Robayt; Bashith, Abdul (Universitas Tribhuwana Tunggadewi, 2025)
This study explores assessment strategies based on validity and reliability in determining the Minimum Competency Criteria (Kriteria Ketuntasan Minimal or KKM) in Islamic religious education. Validity and reliability are two fundamental concepts educators must understand to ensure that the assessment instruments used are dependable and accurate in measuring student competencies. Validity is defined as the degree to which an instrument accurately measures the intended object, while reliability pertains to the consistency of assessment results. The document also emphasizes the importance of conducting trial tests on assessment instruments before widespread implementation to identify and address existing shortcomings. Additionally, this research highlights the use of the Delphi technique as a systematic method to collect and evaluate expert opinions in determining KKM. Through in-depth analysis, the study employs a library research method, reviewing books, journals, and various other literature sources. The findings conclude that the effective application of the Delphi technique, combined with a focus on validity and reliability, can enhance the quality of assessments in Islamic religious education.